2002
DOI: 10.1002/jemt.10250
|View full text |Cite
|
Sign up to set email alerts
|

Microfilaments and microtubules maintain endothelial integrity

Abstract: The endothelium is a highly metabolic monolayer of cells regulating numerous physiological and pathological functions that maintain the permeability and thromboresistant functions of the endothelium. The structure and function of the endothelial cytoskeleton prevents vascular disease by regulating the structure of the endothelium to act as a resting molecular barrier to atherogenic proteins and by becoming an activated layer of migrating cells to repair denuding injuries. The purpose of this review is to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 196 publications
(178 reference statements)
2
67
0
1
Order By: Relevance
“…Recent studies suggest direct involvement of MTs in the regulation of endothelial integrity and wound repair, as depolymerization by the microtubule inhibitors nocodazole and vinblastine results in rearrangement of the actin cytoskeleton, increased stress fiber formation, cell contraction, and permeability (6,28). Here we showed that LIMK1 could induce MTs destabilization (Fig.…”
Section: Limk1 Interacts With Tubulin-supporting
confidence: 64%
“…Recent studies suggest direct involvement of MTs in the regulation of endothelial integrity and wound repair, as depolymerization by the microtubule inhibitors nocodazole and vinblastine results in rearrangement of the actin cytoskeleton, increased stress fiber formation, cell contraction, and permeability (6,28). Here we showed that LIMK1 could induce MTs destabilization (Fig.…”
Section: Limk1 Interacts With Tubulin-supporting
confidence: 64%
“…Dysfunction in cellular shape can cause subsequent vascular hyperpermeability [22] . The cytoskeleton consists of three distinct components: microtubules, actin microfilaments and intermediate filaments [23] , and the former two are associated via linking proteins, which, in turn, interact with these two cytoskeletal components for signaling [24] . As the scaffolding of the cell, the cytoskeleton plays a vital role in cell motility, division, shape maintenance, and signal transduction [24] .…”
Section: Role Of Cytoskeleton In the Regulation Of Endothelial Barriementioning
confidence: 99%
“…CA4P selectively binds to microtubules and depolymerizes tubulin, which results in the activation of RhoGTPase and its associated Rho kinase [34][35][36] (Figure 1). Activation of the Rho/Rho-kinase pathway may cause downstream morphological and/or functional changes in ECs, which can lead to dysmorphism and hyperpermeability: (1) assembly of actin stress fibers and fortified contractility of ECs [24] ; (2) disruption of the VE-cadherin/β-catenin complex to induce the loss of intercellular adhesion and the appearance of paracellular gaps [22] ; (3) blebbing of ECs with regulation of stress-activated protein kinase p38 (SAPK-2/p38) to bring about increased monolayer permeability and resistance to blood flow [36,37] ; and (4) vasoconstriction to give rise to increased geometric resistance to blood flow [38] . In addition, the direct binding of CA4P to tubulin compromises the integrity of cytoskeleton, and morphological changes of endothelial monolayer architecture further deteriorates [7,39] (Figure 1).…”
Section: Mechanisms Of Vda Actionmentioning
confidence: 99%
“…Many signal proteins translocation and activity rely on microtubules; in particular, Rho family GTPases and their regulatory proteins were shown to be tightly associated with polymerized tubulin [Lee, Gotlieb, 2003]. It is not surprising then that the state of actin cytoskeleton, tightly regulated by Rho, depends on microtubule polymerization/depolymerization status.…”
Section: Microtubule Dynamics and Their Role In Endothelial Barrier Mmentioning
confidence: 99%
“…The attachment of cortical ring to membrane and its dynamic rearrangement is modulated by the array of actin and/or membranebinding proteins. The equilibrium between the centripetal and centrifugal forces is a subject to the regulation by several signaling pathways [Lee, Gotlieb, 2003; *Address reprints requests to: Alexander D. Verin, Vascular Biology Center, CB-3210A, Medical College of Georgia, Augusta, Georgia 30912-2500. Office: 706-721-1531;Fax: 706-721-9799; Email: averin@mcg.edu.…”
Section: Introductionmentioning
confidence: 99%